(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
One-member sentences, also known as monosemy sentences or nominative sentences, represent a unique linguistic phenomenon wherein a single word or phrase functions as a complete sentence. Despite their brevity, these structures convey significant meaning and are prevalent across various languages. This paper investigates the structure, usage, and semantic implications of one-member sentences, shedding light on their role in communication and linguistic analysis. Through a comprehensive examination of examples from different languages, we elucidate the diverse forms and functions of these succinct expressions, highlighting their syntactic and semantic complexities.